2005
DOI: 10.1007/s10450-005-5916-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organics on Structure of Water Adsorbed on Activated Carbons

Abstract: Influence of organics on the properties of water adsorbed on carbon and silica gel adsorbents was studied by 1 H NMR spectroscopy, thermal gravimetry, breakthrough dynamics, and quantum chemistry methods. Te behavior of interfacial water depends strongly on the properties of organic solvents, which can remove a major (nonpolar solvents) or minor (polar solvents) portion of water from narrow pores to larger ones of carbon adsorbents. The opposite effect is observed on the interaction of water/organics with sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The adsorption of methane in mesopores also changed because the corresponding f(A) peak shifted from 2 to 1 kJ/mol. A small amount of adsorbed water (5 wt.%) cannot provide effective blocking of mesopores but ice crystallites can change the textural characteristics of the adsorbents because the volume of ice is larger than that of liquid water, and similar effects caused by freezing of adsorbed liquids were observed previously [24,32,[49][50][51][52]. At 200 K pre-adsorbed water more strongly affected the adsorption of methane in narrow micropores (Fig.…”
Section: Structural and Adsorption Characteristicssupporting
confidence: 53%
See 1 more Smart Citation
“…The adsorption of methane in mesopores also changed because the corresponding f(A) peak shifted from 2 to 1 kJ/mol. A small amount of adsorbed water (5 wt.%) cannot provide effective blocking of mesopores but ice crystallites can change the textural characteristics of the adsorbents because the volume of ice is larger than that of liquid water, and similar effects caused by freezing of adsorbed liquids were observed previously [24,32,[49][50][51][52]. At 200 K pre-adsorbed water more strongly affected the adsorption of methane in narrow micropores (Fig.…”
Section: Structural and Adsorption Characteristicssupporting
confidence: 53%
“…2). These results can be also caused by changes in the structure of pores on freezing of adsorbed water [24,[49][50][51][52]. The difference in the effects of pre-adsorbed water on the adsorption of methane at 77.4 and 200 K is observed in the f(A) distribution functions (Fig.…”
Section: Structural and Adsorption Characteristicsmentioning
confidence: 86%
“…The thermoporometry is used for characterizing pore structure from the melting or freezing point depression of a liquid confined in pores, by reason of the added contribution of surface curvature to the phase-transition free energy [20]. The effects of organic solvents on the behaviour of pore water adsorbed onto carbon adsorbents [21][22][23] and mesoporous silica gels [24] were studied by the 1 H NMR method. It was shown that this behaviour depends on molecular size, polarity, polarizability, electron-donor properties, concentration of organic solvents, as well as on the solubility of water in organics and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpolar solvents (immiscible with water) displace pore water from narrow pores of carbon adsorbents more effectively than weakly polar or polar ones (soluble in bulk water). This is due to the different nature of forces giving the main contribution to interaction energy of polar and nonpolar molecules with polar, weakly polar and nonpolar surface sites and adsorbed water molecules forming clusters and droplets near polar sites in pores or at the entrances into the pores [21][22][23]. In the case of silica gel Si-40 with narrow mesopores (close in size to that of MCM-48 studied here) the effects of organics on pore water differ from that observed for activated carbons because of the difference in the structural and adsorption properties of the adsorbents [13,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation